PELATIHAN BAHASA INGGRIS PARIWISATA DI DESA WISATA MELER - Menggo, Sebastianus; Su, Yosefina Rosdiana; Taopan, Rizki Adiputra (JURNAL WIDYA LAKSANA, 2022)
Village tourism objects offer valuable assets that can be utilized by the village government in accelerating the welfare of the village community. The utilization of these assets cannot be separated from English communication competence. English competence has an effect on the quality of tourist services, particularly for foreign visitors. This service activity aims to improve communication skills in the English language of tourism and awareness of the essence of hospitality toward twenty-five persons in Meler village tourism. The service was carried out at the traditional house of Meler village and Meler tourist village cottage for four months (March - June 2021), once a week. The methods used to achieve this goal are lectures, question and answer, discussion, role-playing, demonstrations and personal presentation. The results show that the training participants understand the role of hospitality in tourism services and increase the fluency of communicating English in the tourism field.